Reduced plasma fibrin clot permeability and susceptibility to lysis are associated with increased risk of postthrombotic syndrome. (18th February 2016) - Siudut, J.; Grela, M.; Wypasek, E.; Plens, K.; Undas, A.
Abstract : Essentials The postthrombotic syndrome (PTS) is a common complication of deep vein thrombosis (DVT). Plasma fibrin clot properties were assessed in patients followed for 1 year after DVT. Lower fibrin clot permeability and impaired lysability can predispose patients to PTS. Severe PTS is associated with more unfavorable clot variables. Summary: Background: The postthrombotic syndrome (PTS) is a severe complication of deep vein thrombosis (DVT). Reduced plasma clot permeability and lysability have been linked to DVT and residual vein obstruction. Objectives: We investigated whether altered fibrin clot properties are associated with the occurrence of PTS. Patients and Methods: Plasma fibrin clot permeability (Ks ) and lysability were investigated in a cohort of 197 consecutive patients aged 18 to 65 years recruited 3 months following the first‐ever DVT. Patients with severe thrombophilia or comorbidities known to adversely affect clot phenotype were ineligible. Results: During a 1‐year follow‐up PTS developed in 48 (24%) patients, who were characterized by lower Ks, prolonged fibrin clot lysis time (CLT) and slower release of D‐dimer from clots (D–Drate ), together with higher plasma D‐dimer, C‐reactive protein and thrombin‐activatable fibrinolysis inhibitor (TAFI). No PTS‐associated differences in fibrinogen, thrombin generation, factor VIII, other fibrinolysis proteins and the quality of anticoagulation were observed. Ks ( r = −0.71), CLT ( r = 0.45), D–Drate ( r = −0.30) and TAFI activity ( r = 0.38) were associated with the Villalta scale (all P < 0.05). Recurrent VTE occurred also more commonly in PTS patients during follow‐up and the 26 (13.2%) patients had lower Ks, longer CLT and lower D–Drate (all P < 0.05). A multivariate model adjusted for age, body mass index, fibrinogen and glucose showed that independent predictors of PTS were idiopathic DVT, plasma D‐dimer, Ks, D–Drate, tissue plasminogen activator and TAFI activity. Conclusions: This study demonstrates that formation of more compact fibrin clots displaying impaired susceptibility to lysis predisposes to PTS.